Limited behavioural effects of ocean acidification on a Mediterranean anemone goby (Gobius incognitus) chronically exposed to elevated CO2 levels. (November 2022) - Spatafora, Davide; Cattano, Carlo; Aglieri, Giorgio; Quattrocchi, Federico; Turco, Gabriele; Quartararo, Giulia; Dudemaine, Jeanne; Calosi, Piero; Milazzo, Marco
Abstract: An in situ reciprocal transplant experiment was carried around a volcanic CO2 vent to evaluate the anti-predator responses of an anemone goby species exposed to ambient (∼380 μatm) and high (∼850 μatm) CO2 sites. Overall, the anemone gobies displayed largely unaffected behaviors under high-CO2 conditions suggesting an adaptive potential of Gobius incognitus to ocean acidification (OA) conditions. This is also supported by its 3-fold higher density recorded in the field under high CO2 . However, while fish exposed to ambient conditions showed an expected reduction in the swimming activity in the proximity of the predator between the pre- and post-exposure period, no such changes were detected in any of the other treatments where fish experienced acute and long-term high CO2 . This may suggest an OA effect on the goby antipredator strategy. Our findings contribute to the ongoing debate over the need for realistic predictions of the impacts of expected increased CO2 concentration on fish, providing evidence from a natural high CO2 system. Graphical abstract: Image 1 Highlights: This is the first assessment in the wild of behavioural responses of fish acutely and chronically exposed to elevated CO2 . High density of anemone goby fish was recorded at high-CO2 levels off a volcanic CO2 vent in Vulcano island (Italy). Acute and chronic exposure to elevated CO2 did not affect most of the behaviours in adult G. incognitus. Behavioural plasticity occurred under ocean acidification conditions suggesting potential local adaptation.